0070 Evaluation Of Simulation As A Tool To Teach Healthcare Undergraduates Acute Care Competencies. (1st November 2014) - Wee, Lisa; Matthews, Rachel; Smith, Michael
Abstract : Background: The National Confidential Enquiry into Patient Outcome and Death found evidence that junior medical and nursing staff lack competencies to deal with acutely unwell patients. 1 The training of healthcare undergraduates in the recognition, assessment and management of acutely unwell patients is suboptimal. 2, 3 We developed a simulation session for 3 rd year medical and nursing students from the University of Manchester to address this problem using scenarios based on existing problem based learning (PBL) cases. Methodology: Students participated and observed 2 of 4 potential scenarios, including COPD exacerbation, hypoglycemia, acute abdominal pain and a myocardial infarction scenario encompassing communication with a distressed relative. Learning objectives included ABCDE-assessment, focused history taking, communication skills, prescribing and multidisciplinary teamwork. Each simulation session included a pre-brief and extended debrief by a multidisciplinary faculty (medical education pharmacist, doctors, clinical and communication skills tutors). Debriefing focused on areas found challenging for participants or where learning outcomes were not met. Written evaluation data was collected from all participants, including specific responses captured using modified Likert scales. Results: Feedback data was collected for 87 medical students and 21 nursing students. A number of themes emerged from the debriefing, including the challenge of applying knowledge in a time-sensitive or distracting environment, prioritisation and the ability to perform a focused patient assessment. Students found the experience of working within a multidisciplinary team and the detailed feedback on how to perform a focused patient assessment most useful. Participants reported that the scenarios were relevant to practice (mean score 3.86/4), teaching was effective (3.82) and that they had increased confidence in managing future situations (3.55). Conclusion: Simulation sessions were universally well received. Our simulation tool could teach the necessary competencies in acute patient care and also assess the impact of further targeted teaching, with integration into the undergraduate curriculum. References: NCEPOD. An acute problem? A report of the National Confidential Enquiry into Patient Outcome and Death (NCEPOD) London: NCEPOD; 2005 Perkins GD, Barrett H, Bullock I, et al . (2005) The Acute Care Undergraduate Teaching (ACUTE) Initiative: consensus development of core competencies in acute care for undergraduates in the United Kingdom. Intensive Care Med 31:1627–1633 Smith C, Perkins G, Bullock I, Bion J. Undergraduate training in the care of the acutely ill patient: a literature review. Intensive Care Med 2007;33:901–907